2020
DOI: 10.37983/ijdm.2020.2204
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in metallurgy and design of rotary endodontic instruments: a review

Abstract: A variety of instruments are available for the extirpation of the pulp and the instrumentation and preparation of the root canal. Recently, nickel-titanium (NiTi) alloy is utilised for the manufacturing of endodontic instruments. Compared to other metals, these alloys are highly flexible, which significantly enhances ease of canal shaping. This review article gives an account in the advances of NiTi endodontic instruments with an emphasis on metallurgical, mechanical properties, the design features of each gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
2
0
2
Order By: Relevance
“…This finding is in accordance with the results of a research on a significant reduction of surface irregularities of electropolished instruments [3]. Electropolishing creates a homogeneous oxide layer during the production process, which reduces the appearance of surface defects and increases resistance to corrosion and fracture [27]. Electropolished surface of instruments is visibly brighter than the untreated surface [26].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This finding is in accordance with the results of a research on a significant reduction of surface irregularities of electropolished instruments [3]. Electropolishing creates a homogeneous oxide layer during the production process, which reduces the appearance of surface defects and increases resistance to corrosion and fracture [27]. Electropolished surface of instruments is visibly brighter than the untreated surface [26].…”
Section: Discussionsupporting
confidence: 88%
“…Subsequent heat treatment of finished Ni-Ti instruments (HyFlex) potentially offers the most promising method of manufacturing rotating instruments [27]. These instruments do not have the shape memory that traditional Ni-Ti instruments have, and a special thermomechanical procedure significantly increases their flexibility [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current results of studies on the impact of sterilization on the occurrence of corrosion are contradictory and there is no clear position on this issue. Multiple sterilization cycles can cause corrosive changes on the surface of Ni-Ti files due to changes in the surface layer of titanium oxide [16,17]. However, it has also been observed that after sterilization, resistance to cyclic fatigue and torsional stress increases in certain types of Ni-Ti instruments because the sterilization process acts as a form of heat treatment [18].…”
Section: Discussionmentioning
confidence: 99%